2016
DOI: 10.1371/journal.pone.0167635
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Tryptophan Maize Near Isogenic Lines Adapted to Temperate Regions through Marker Assisted Selection - Impediments and Benefits

Abstract: Breeding program aimed at converting standard maize inbred lines to their quality protein maize (QPM) counterparts for growing in temperate climate is being conducted at Maize Research Institute (MRI). The objective of the research presented herein was to develop QPM versions of two commercial ZP inbreds through marker assisted selection (MAS) with opaque2 specific molecular markers, while maintaining their good agronomic performances and combining abilities. Donor line was a tropical QPM line CML 144. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…As one way to avert protein malnutrition, many QPM conversion studies were carried out previously for dent corn (Babu et al, 2005; Gupta et al, 2009, 2013; Sofi et al, 2009; Jompuk et al, 2011; Krishna et al, 2017; Surender et al, 2017). Common challenges in QPM conversion programs included incomplete recovery of vitreous endosperm (modification), discontinuation of certain crosses from poor seed set and failure to improve lysine and tryptophan content (Moro et al, 1996; Prasanna et al, 2001; Vivek et al, 2008; Kostadinovic et al, 2016). Since popcorn kernels naturally have a very high proportion of vitreous endosperm (Figure 3), and this is the kernel region in which starch can melt during the popping process, complete endosperm modification is likely of paramount importance in QPM conversion into a popcorn background.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As one way to avert protein malnutrition, many QPM conversion studies were carried out previously for dent corn (Babu et al, 2005; Gupta et al, 2009, 2013; Sofi et al, 2009; Jompuk et al, 2011; Krishna et al, 2017; Surender et al, 2017). Common challenges in QPM conversion programs included incomplete recovery of vitreous endosperm (modification), discontinuation of certain crosses from poor seed set and failure to improve lysine and tryptophan content (Moro et al, 1996; Prasanna et al, 2001; Vivek et al, 2008; Kostadinovic et al, 2016). Since popcorn kernels naturally have a very high proportion of vitreous endosperm (Figure 3), and this is the kernel region in which starch can melt during the popping process, complete endosperm modification is likely of paramount importance in QPM conversion into a popcorn background.…”
Section: Discussionmentioning
confidence: 99%
“…Poor seed set has been observed in other QPM conversions throughout selection and can lead to the loss of targeted crosses (Kostadinovic et al, 2016). This phenomenon may be attributable to incompatibility between pollen and style.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To alleviate these setbacks, CIMMYT employed a large-scale breeding program involving multiple opaque-2 varieties and selected moderately improved vitreousness levels through back-crossed generations. Along with the opaque-2 mutation, CIMMYT observed the necessary introgression of unknown amino acid and endosperm vitreousness restorer genes through phenotypic selection for the biofortified, vitreous QPM end product (Babu et al, 2005;Sofi et al, 2009;Panda et al, 2010;Mbuya et al, 2011;Babu and Prasanna, 2014;Surender et al, 2014;Kostadinovic et al, 2016;Krishna et al, 2017). Though most amino acid and endosperm modifier genes remain unidentified, QTL studies have suggested that endosperm restorer genes are located on Chromosomes 1, 5, 7, and 9 (Holding et al, 2008(Holding et al, , 2011Babu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%